Analysis of the services of the project of government in line with regard to the limits and normatividad stipulated by the national program of service to the citizen in the public sector (2013)
The companies of the public sector have recognized the importance of satisfying the needs of service of the citizens, since they are a fundamental part of the state-owned companies, for which they have developed projects that contribute to better the presentation of the same one, as the project of Government In Line, Whose services are orientated to solve steps, requests and information for the citizens, being for it important to analyze if the project is aligned by the stipulated by the National Program of Service to the Citizen, who regulates the mechanisms, processes and procedures for the service in the public entities. The companies of the public sector in order infrastructure and human beings increase the confidence of the citizens towards these entities, by means of the effective management of the requests, attention adapted to the citizens, excellent technological resources, or if for the opposite the project needs of improvements changes that allow to give an excellent service to the citizen.